Pengaruh Aplikasi Finishing Yakisugi Terhadap Sifat Fisis dan Mekanis Kayu Rajumas (Duabanga moluccana): The Effect of Yakisugi Finishing Application on the Physical and Mechanical Properties of Rajumas Wood (Duabanga moluccana) - Amir, Hafidzah Amani; Lestari, Andi Tri; Ningsih, Rima Vera (PERENNIAL, 2025)
This study aims to examine the influence of yakisugi surface charring treatment on the physical and mechanical properties of Rajumas wood (Duabanga moluccana). The method involved surface burning for 0 (control), 20, 40, and 60 seconds using a butane gas torch. Tests were conducted on moisture content, density, shrinkage, water absorption, thickness swelling, modulus of rupture (MoR), and modulus of elasticity (MoE). Statistical analysis using one-way ANOVA followed by Tukey’s HSD test (α = 0.05) was performed to evaluate treatment effects. The results showed that burning duration affected both physical and mechanical properties of Rajumas wood. Longer burning durations improved dimensional stability by reducing moisture content, water absorption, and swelling; however, mechanical strength (MoR and MoE) tended to decrease at 60 seconds due to partial thermal degradation of cell wall polymers. Moderate exposure (20–40 seconds) provided an optimal balance between improved stability and acceptable strength retention. This study highlights the novel application of Yakisugi to a fast-growing tropical hardwood, offering a sustainable surface modification technique for enhancing durability and performance in non-structural wood applications.